On the relationship between monthly mean surface temperature and tornado days in the United States - Kimberly A. Hoogewind; Vittorio A. Gensini; Harold E. Brooks (npj Climate and Atmospheric Science)
Abstract Correlation was examined between detrended monthly surface temperature and monthly [E]F-1+ tornadoes and tornado days for several contiguous US regions during the period 1954–2022. This relatively simple, yet robust, analysis indicated that regional temperature fluctuations are moderately-to-strongly correlated with tornado days during some months and in certain regions. In general, surface temperatures during boreal cool (warm) season had a positive (negative) correlation with tornado days. Implications for using a continuous, simple scalar variable such as surface temperature for tornado prediction are discussed, as well as the potential utility for understanding changes in tornado frequency due to climate variability and change.